2019
DOI: 10.1021/acsami.8b22724
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Property of Hydrogels and the Presence of Adipose Stem Cells in Tumor Stroma Affect Spheroid Formation in the 3D Osteosarcoma Model

Abstract: Osteosarcoma is one of the most common metastatic bone cancers, which results in significant morbidity and mortality. Unfolding of effectual therapeutic strategies against osteosarcoma is impeded because of the absence of adequate animal models, which can truly recapitulate disease biology of humans. Tissue engineering provides an opportunity to develop physiologically relevant, reproducible, and tunable in vitro platforms to investigate the interactions of osteosarcoma cells with its microenvironment. Adipose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 52 publications
0
36
0
Order By: Relevance
“…Synthetic hydrogels such as polyethylene glycol (PEG), 3 2-hydroxyethyl methacrylate (HEMA)-based hydrogels, 4 poly(oxazoline)s (POx), 5 or polyacrylamide (PAAm), as well as naturally derived hydrogels such as alginate, gelatin, collagen, or fibrin matrices, [6][7][8][9] have been used in various biomedical appli-cations. 1 Frequently, these include the delivery of cells, [10][11][12][13][14] growth factors, [15][16][17] or drugs, [18][19][20][21][22] in vitro tissue and tumor models, [23][24][25] and tissue engineering (TE) matrices. 2,[26][27][28][29][30] The role of biopolymer hydrogels in TE is to chemically and physically mimic the extracellular matrix (ECM) environment to facilitate controlled cell adhesion, proliferation, differentiation, and matrix remodeling.…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic hydrogels such as polyethylene glycol (PEG), 3 2-hydroxyethyl methacrylate (HEMA)-based hydrogels, 4 poly(oxazoline)s (POx), 5 or polyacrylamide (PAAm), as well as naturally derived hydrogels such as alginate, gelatin, collagen, or fibrin matrices, [6][7][8][9] have been used in various biomedical appli-cations. 1 Frequently, these include the delivery of cells, [10][11][12][13][14] growth factors, [15][16][17] or drugs, [18][19][20][21][22] in vitro tissue and tumor models, [23][24][25] and tissue engineering (TE) matrices. 2,[26][27][28][29][30] The role of biopolymer hydrogels in TE is to chemically and physically mimic the extracellular matrix (ECM) environment to facilitate controlled cell adhesion, proliferation, differentiation, and matrix remodeling.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the tumor tissue is more appropriate to be treated as an organ but not a mass of transformed epithelial cells (1)(2)(3). More and more researchers have been investigating into tumor microenvironment and gained more and more achievement revealing the effect of tumor micro-environment on various kinds of cancers (4,5). Yoshihara et al developed a new algorithm that can infer tumor cellularity using transcriptional profiles of cancer samples and it can estimate the relative amount of the stromal and immune cells that form the main non-tumor components by outputting ESTIMATE score as well as Stromal score and Immune score (6).…”
Section: Introductionmentioning
confidence: 99%
“…3, 4, 5, 6). It is well established that the presence of a bioactive 3D environment provides a higher stimulation of genes compared to a simple inducing medium, assuming high relevance for the reproduction of an in vitro more closely predictive osteosarcoma model 58,59 . In fact, many studies reported how the use of conventional 2D approaches failed to explain tumour cell biology, because they did not mimic real macrostructure, complexity (tumourstroma interactions) and heterogeneity of the tumour microenvironment 28,60 .…”
Section: Discussionmentioning
confidence: 99%